2016
DOI: 10.1002/acn3.332
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Friedreich ataxia: quantitative characterization over 5 years

Abstract: ObjectiveFriedreich ataxia (FRDA) is a progressive neurodegenerative disorder of adults and children. This study analyzed neurological outcomes and changes to identify predictors of progression and generate power calculations for clinical trials.MethodsEight hundred and twelve subjects in a natural history study were evaluated annually across 12 sites using the Friedreich Ataxia Rating Scale (FARS), 9‐Hole Peg Test, Timed 25‐Foot Walk, visual acuity tests, self‐reported surveys and disability scales. Cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
158
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 117 publications
(167 citation statements)
references
References 18 publications
6
158
3
Order By: Relevance
“…Interim analyses of this natural history cohort have been reported previously,5, 6, 8, 9, 10, 11, 12, 13 a subset of which has included assessments of glucose homeostasis 5, 8. The present study is a cross‐sectional analysis including self‐reported health history and medications, physician‐administered performance metrics, and neurological testing.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Interim analyses of this natural history cohort have been reported previously,5, 6, 8, 9, 10, 11, 12, 13 a subset of which has included assessments of glucose homeostasis 5, 8. The present study is a cross‐sectional analysis including self‐reported health history and medications, physician‐administered performance metrics, and neurological testing.…”
Section: Methodsmentioning
confidence: 97%
“…811 individuals with FA were enrolled between 2004 and 2015, and re‐evaluated annually at 12 international sites 6. Information from the most recent visit was used in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations